Fruits: importance of preharvest factors, maturity stage at harvest & postharvest treatments - Osman, Azizah (2012)
Fruits have been part of the human diet since the dawn of history but their nutritional importance has only been recognised in recent times. Commerce in fruits began in the 1980’s when awareness on their nutritional importance has risen. Since then, its demand in the international markets has also increased tremendously. Malaysia went through a series of phases to develop its fruit industry to reach its present status- able to be leading exporter of some tropical fruits. Quality of fruits could not be improved once harvested but it can be preserved by slowing down the rate of undesirable changes which leads to a reduction in their quality. Postharvest qualities of fruits are affected by pre-harvest factors, stage of maturity at harvest and postharvest factors because of the many physico-chemical changes taking place during the life span of the fruit. The rate at which these changes occur can be manipulated by careful management of the postharvest handling system for quality maintenance and shelf-life extension of the fruits. Due to changes in consumers’ life style especially in urban areas, convenient and ready-to-eat fresh-cut fruits are becoming more popular in the last few decades. However, there are problems associated to it which requires studies to be carried out to overcome them. Apart from the increasing demands for these fresh cut fruits, there is also a trend during the same period of time, where consumers consume fruits not only for its nutritional contents but emphasis is also given to its functional properties.